2015
DOI: 10.3892/mmr.2015.3709
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive analysis of differentially expressed genes and pathways in abdominal aortic aneurysm

Abstract: Abstract. The current study aimed to investigate the molecular mechanism underlying abdominal aortic aneurysm (AAA) via various bioinformatics techniques. Gene expression profiling analysis of differentially expressed genes (DEGs) between AAA samples and normal controls was conducted. The Database for Annotation, Visualization and Integrated Discovery tool was utilized to perform Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes analyses for DEGs and clusters from the protein-protein interaction (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…The current application of genome analysis may provide several new insights into the area. According to the gene expression profiling analysis of differentially expressed genes (DEGs) between AAA samples and normal controls, a total of 436 DEGs were identified using Gene Ontology (GO) and KEGG analyses [42], and four different clusters were identified from the protein-protein interaction network [42]. In addition to the known and traditional pathways involved in the response to viral infection and the defense response indicative of the role of inflammation during AAA, one of the four clusters was associated with mitochondria-associated functions and the oxidative phosphorylation subpathway [42]; a potential role of mitochondrial function in the pathogenesis of AAA was thus proposed.…”
Section: A Potential Role Of Mitochondrialmentioning
confidence: 99%
“…The current application of genome analysis may provide several new insights into the area. According to the gene expression profiling analysis of differentially expressed genes (DEGs) between AAA samples and normal controls, a total of 436 DEGs were identified using Gene Ontology (GO) and KEGG analyses [42], and four different clusters were identified from the protein-protein interaction network [42]. In addition to the known and traditional pathways involved in the response to viral infection and the defense response indicative of the role of inflammation during AAA, one of the four clusters was associated with mitochondria-associated functions and the oxidative phosphorylation subpathway [42]; a potential role of mitochondrial function in the pathogenesis of AAA was thus proposed.…”
Section: A Potential Role Of Mitochondrialmentioning
confidence: 99%
“…Mitochondrial dysfunction has been associated with arterial aneurysm formation, but most studies have analysed abdominal aortic aneurysms (AAAs) rather than genetic thoracic aneurysmal aorta syndromes. For example, AAAs show differential expression of a number of genes associated with mitochondrial function and oxidative phosphorylation 4 and peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC1α) gene expression is decreased in human AAA and angiotensin (Ang) II-induced AAA in mice. Similarly, the intima/media layer of AAA vessels showed reduced expression of a number of markers of mitochondrial biogenesis, including PGC1α, ATP synthase, and citrate synthase.…”
mentioning
confidence: 99%
“…Egr-1 also regulates the expression of genes related to the development of vascular diseases ( 14 ). Bioinformatics analysis showed that Egr-1 is a key transcription factor in the formation and pathogenesis of AAA ( 15 ). Egr-1 was found to be involved in thrombus formation and the inflammatory pathogenesis of AAA.…”
Section: Discussionmentioning
confidence: 99%